ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2021
DOI: 10.1109/icassp39728.2021.9414342
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Emotion Classification Using Graph Signal Processing

Abstract: The key role of emotions in human life is undeniable. The question of whether there exists a brain pattern associated with a specific emotion is the theme of many affective neuroscience studies. In this work, we bring to bear graph signal processing (GSP) techniques to tackle the problem of automatic emotion recognition using brain signals. GSP is an extension of classical signal processing methods to complex networks where there exists an inherent relation graph. With the help of GSP, we propose a new framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…A number of studies have also shown promising results in applying GSP techniques in classification, dimensionality reduction, and denoising of EEG signals [32][33][34][35][36][37]. In [32], network harmonics of the brain structural connectivity graph are derived for tracking fast spatiotemporal cortical dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have also shown promising results in applying GSP techniques in classification, dimensionality reduction, and denoising of EEG signals [32][33][34][35][36][37]. In [32], network harmonics of the brain structural connectivity graph are derived for tracking fast spatiotemporal cortical dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Concluding remarks are given in Section 6, while some technical details are deferred to the appendices. This journal paper offers a more thorough treatment of online discriminative graph learning relative to its short conference precursors [1,2]. This is achieved by means of expanded technical details, discussions and insights, as well as through more comprehensive performance evaluation studies with synthetic and real data experiments.…”
Section: Proposed Approach and Contributionsmentioning
confidence: 99%
“…This is achieved by means of expanded technical details, discussions and insights, as well as through more comprehensive performance evaluation studies with synthetic and real data experiments. In particular, focus in [1] is on emotion classification from EEG signals (the subject of Section 5.3), while [2] deals with online topology identification without a classification task in mind; see also Remark 2. Notational conventions.…”
Section: Proposed Approach and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior information of MTMC EEG signal classification [9] can also be utilised using GSP by embedding smoothness of signal variation between nodes and bandlimitedness in the graph spectral domain etc. [23], [24] Motivated by this, learning the mental task based functional brain connectivity from multi channel EEG signal using GSP technique is addressed in this paper. We propose graph signal representation of EEG signals corresponding to each task, where each channel corresponds to the nodes of the graph representing the different regions of the brain and the observations over all channels correspond to the graph signal.…”
Section: Introductionmentioning
confidence: 99%